Assessment of antimicrobial efficacy of chitosan-based tetracycline gel on periodontal pathogens: An In vitro study - Mohammad Jalaluddin; Avdhoot Kulkarni; Kavita Raj; Deesha Kumari; Konsam Bidya Devi; N S Vineeth (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of the current research was to evaluate the antimicrobial effectiveness of chitosan-based tetracycline gel on periodontal pathogenic microorganisms. Materials and Methods: Preparation of chitosan-based tetracycline gel of 0.7% and 1% was done. In addition, 0.2 g of chitosan, 1% citric acid, and then 0.35 g of tetracycline in that order was added. Furthermore, 0.5 g of the tetracycline, which had been subjected to crushing and then stirring in a glass beaker to obtain a homogeneous gel was subjected to insertion into the syringe sterile. Such material prepared at the instance will attempt to investigate the sensitivity of bacteria in Surabaya to preserve the steadiness of the material. Evaluation of antimicrobial outcomes of chitosan-based tetracycline gel was performed against Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis. Results: The highest region of inhibition was noted at 28.26 ± 1.08 mm, 23.98 ± 2.02 mm against A. actinomycetemcomitans and P. gingivalis at 1% chitosan-based tetracycline gel, in pursuit by the 0.7% chitosan-based tetracycline gel at 15.12 ± 0.16 mm and 14.48 ± 1.22 mm region of inhibition, followed by a control group that exhibited 4.16 ± 1.29 mm and 4.82 ± 1.20 mm regions of inhibition against either of the pathogens. Conclusion: To conclude, the chitosan-based tetracycline gel is efficient in restraining the growth of A. actinomycetemcomitans and P. gingivalis bacteria. Tetracycline 1% gel-based chitosan exhibited maximum antibacterial action since it depicted the maximum inhibition region diameter versus tetracycline gel 0.7%.